Keanekaragaman dan Kepadatan Populasi Cacing Tanah di Perkebunan Jeruk Organik Kecamatan Karangploso Kabupaten Malang - Hurriatun Nisa; Hari Santoso; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2020)
Earthworm is one of the soil fauna that plays an important role in soil fertility. The density of earthworm is influenced by the physical factor-kima soil. Research aims to determine the diversity and density of earthworm in organic citrus plantation in Karangploso district of Malang. The method of research conducted in a systematic, systematised quantitative use transect line of 50 m each line is taken 10 dots is 5 m with 3 times repeated at each station, the station 1 Citrus Garden fruitful (KJB), Station 2 Citrus groves have not been fruitful (KJBB). Observations were conducted in May 2019. The results of the research found 3 genus of earthworm species Pheretima, Pontoscolex and Microscolex. The highest density of earthworm in organic citrus plantations is a genus of Microscolex 0.348 individual/m2; The lowest density genus Pontoscolex 0.124 individual/m2. Earthworm density in organic citrus plantations is a genus Pontoscolex 0.156 individual/m2; Lowest density genus Pheretima 0.042 individual/m2. The ecological type of earthworm in this plantation is epigeic and anesic type. The correlation between the physics-chemistry factor of soils with earthworm density indicates a positive correlation in the genus Pheretima with temperature, humidity and soil pH. The genus Pontoscolex is positively correlated with temperature, moisture content and soil pH. In the genus Microscolex correlated positively with temperature, humidity and moisture content. The physical-chemical factor of the soil has a close connection with the existence of earthworm where strong correlation in temperature and humidity. Keywords: earthworms, density, orange plantations ABSTRAK Cacing tanah merupakan salah satu fauna tanah yang berperan penting dalam kesuburan tanah. Kepadatan cacing tanah dipengaruhi oleh faktor fisika-kima tanah. Penelitian bertujuan untuk mengetahui keanekaragaman dan kepadatan cacing tanah di perkebunan jeruk organik kecamatan Karangploso Malang. Metoda penelitian dilakukan secara diskriptif kuantitatif secara sistemastis menggunakan transek garis sepanjang 50 m setiap garis diambil 10 titik berjarak 5 m dengan dilakukan 3 kali ulangan pada setiap stasiun, Stasiun 1 kebun jeruk berbuah (KJB), stasiun 2 kebun jeruk belum berbuah (KJBB). Pengamatan dilakukan pada bulan Mei 2019. Hasil penelitian ditemukan 3 genus cacing tanah yakni genus Pheretima, Pontoscolex dan Microscolex. Kepadatan cacing tanah tertinggi di perkebunan jeruk organik adalah genus Microscolex 0,348 individu/m2; kepadatan terendah genus Pontoscolex 0,124 individu/m2. kepadatan cacing tanah di perkebunan jeruk organik adalah genus Pontoscolex 0,156 individu/m2 ; kepadatan terendah genus Pheretima 0,042 individu/m2. Tipe ekologi cacing tanah pada perkebunan ini yaitu tipe epigeik dan anesik. Korelasi antara faktor fisika-kimia tanah dengan kepadatan cacing tanah menunjukkan korelasi positif pada genus Pheretima dengan suhu, kelembaban dan pH tanah. Pada genus Pontoscolex berkolerasi positif dengan suhu, kadar air dan pH tanah. Pada genus Microscolex berkolerasi positif dengan suhu, kelembaban dan kadar air. Faktor fisika-kimia tanah memiliki hubungan erat dengan keberadaan cacing tanah dimana korelasi yang kuat pada suhu dan kelembaban. Kata kunci: cacing tanah, kepadatan, perkebunan jeruk